Au seuil de l’intimité conjugale : la chambre nuptiale à la Belle Époque - Aïcha Salmon (Genre & Histoire)
In nineteenth-century France, marriage had to be consummated on the wedding night. This entry into legitimate sexuality was spatially circumscribed to a particular place, designated by the generic expression of the bridal chamber. The first sexual act of the marital relationship was supposed to take place there: this location was thus decisive in the construction of the bonds between husband and wife. It largely determined the way in which the bridal chamber and the bed of the newlyweds were thought of, conceived, prepared, and occupied by them. This essay focuses on the representations of the bridal chamber, but also on the concrete experiences of the spouses who spend their first night there, which both reveal that the difference between the sexes played a major role. in the imagination and in practice. It presents the main characteristics of the bridal chamber in terms of its location, function and decoration (I), then it looks at the tensions that arise when the nuptial chamber was supposed to give more privacy to spouses and become more closed to outsiders (II).